2007
DOI: 10.1287/moor.1070.0259
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Product Forms for Lévy-Driven Fluid Networks

Abstract: We study stochastic tree fluid networks driven by a multidimensional Lévy process. We are interested in (the joint distribution of) the steady-state content in each of the buffers, the busy periods, and the idle periods. To investigate these fluid networks, we relate the above three quantities to fluctuations of the input Lévy process by solving a multidimensional Skorokhod reflection problem. This leads to the analysis of the distribution of the componentwise maximums, the corresponding epochs at which they a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…This result for a single queue has been extended more recently to the network setting [18,29]; it was found that for (s, t) ∈ R 2 + ,…”
Section: A(s T) = A(t) − A(s) Denote the Amount Of Traffic Generatedmentioning
confidence: 85%
See 1 more Smart Citation
“…This result for a single queue has been extended more recently to the network setting [18,29]; it was found that for (s, t) ∈ R 2 + ,…”
Section: A(s T) = A(t) − A(s) Denote the Amount Of Traffic Generatedmentioning
confidence: 85%
“…For the important case of spectrally-positive Lévy input (that is, the driving Lévy process does not have negative jumps), the joint Laplace transform of the stationary buffer contents has been found for a broad class of network structures, including tandem queues [18,19,29]. With the transforms being available, one may attempt to use these in order to explicitly find the joint distribution of the stationary buffer contents.…”
Section: Introductionmentioning
confidence: 99%
“…The results concerning the joint distribution of the steady state of the workloads were studied in a more general network setting in, for example, [9]. These results play an important role for our analysis and are therefore summarized in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…The transform can be obtained for tandem and feed-forward networks with decreasing service rates (in the direction of flow), see e.g. Kella and Whitt (1992a) and Debicki, Dieker and Rolski (2007). In such networks, if one queue is empty then all the queues preceding it are empty as well.…”
mentioning
confidence: 99%